Diseño y construcción de un prototipo de máquina CNC con acoplamiento FDM para la fabricación de piezas en 3D (2021)
Computerized numerical control (CNC) machine tools configure a technology and a high degree of efficiency, accuracy, uniformity and machining in the manufacture of parts, on the other hand, 3D printing is not something new in the technological world, since 3-dimensional objects are made for a long time for replication and mass production. This is through different types of 3D printing technologies such as FDM (Fused deposition modeling). This work is based on the design and construction of a CNC machine with a coupling of an FDM system for the manufacture of 3D parts in order to reduce the costs of extra machines for laboratory practices at the Antonio Nariño University (UAN) Headquarters Villavicencio, which does not have machine tools of this type. The machine will allow to obtain physical models of designs made in CAD (computer-aided design) and the system will consist of a physical structure that will allow movements in the three axes (x, y, z). This work describes each of the phases for the construction of the physical structure and the parameters of the information analysis software.